2014
DOI: 10.1158/0008-5472.can-13-1423
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Catabolism: A Novel Metabolic Pathway Contributing to Glioblastoma Growth

Abstract: The relevance of cysteine metabolism in cancer has gained considerable interest in recent years, largely focusing on its role in generating the antioxidant glutathione. Through metabolomic profiling using a combination of high-throughput liquid and gas chromatography–based mass spectrometry on a total of 69 patient-derived glioma specimens, this report documents the discovery of a parallel pathway involving cysteine catabolism that results in the accumulation of cysteine sulfinic acid (CSA) in glioblastoma. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
92
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 36 publications
10
92
0
1
Order By: Relevance
“…15,16 Abnormal thiol disulphide homeostasis states are involved in the pathogenesis of many kinds of diseases, including diabetes, 17 cardiovascular disease, 18 cancer, 19 chronic kidney disease, 20 and rheumatoid arthritis. 21 One side of this double-sided balance, namely thiols, has been measurable since 1979.…”
mentioning
confidence: 99%
“…15,16 Abnormal thiol disulphide homeostasis states are involved in the pathogenesis of many kinds of diseases, including diabetes, 17 cardiovascular disease, 18 cancer, 19 chronic kidney disease, 20 and rheumatoid arthritis. 21 One side of this double-sided balance, namely thiols, has been measurable since 1979.…”
mentioning
confidence: 99%
“…11,12) Although thiol/disulfide homeostasis has been increasingly studied in many disorders, no studies thus far have investigated thiol/disulfide homeostasis in cancer patients who suffered from anthracycline-induced cardiotoxicity. 13,14) Thus, we aimed to evaluate whether thiol/disulfide homeostasis may plav a role in the protection of myocardial cells from anthracycline-induced toxicity as a novel oxidative stress parameter.…”
mentioning
confidence: 99%
“…It is hypothesized that reduced CDO1 expression may provide an advantage to cancer cells to survive under an oxidative stress environment. However, a causative relationship has not been established so far, and the opposite effect of CDO1 expression in cancer cell growth has also been reported recently (47). A few studies conducted in genetic Cdo1-knockout mice revealed that whole-body complete CDO1 ablation caused more complex metabolic changes and subsequent pathological effects in mice.…”
Section: Discussionmentioning
confidence: 99%